Characterization of Bacteriocin-Producing Lactic Acid Bacteria Strain N1-33 Isolated from Edible Fermented Bamboo Shoot - Melaku Alemu; Panthipa Laemkom; Katsumi Doi; Sadahiro Ohmomo; Mizuo Yajima; Sunee Nitisinprasert (Agriculture and Natural Resources, 2006)
Lactic acid bacteria (LAB) strain N1-33, isolated from edible fermented bamboo shoot, displayed broad spectrum of inhibitory activity against LAB and other Gram-positive food spoilage and pathogenic bacteria. On the basis of its physiological and biochemical properties together with 16S rRNA sequence analysis, N1-33 was identified as Enterococcus faecalis. It was cultivated in MRS broth at 30°C to early stationary growth phase and the resulting cell-free culture supernatant (CS) showed a maximum inhibitory activity of 12800 AU/ml against Lactobacillus sakei subsp. sakei JCM 1157T, with bactericidal mode of action and concomitant cell lysis. The antibacterial activity of the CS was completely destroyed with proteinase K and partially inactivated with pepsin treatments. Moreover, the study on its physicochemical stability indicated that it was heat tolerant up to 121°C and remained bioactive over a pH range of 2-11. Thus, the spectrum of inhibitory activity, sensitivity to proteolytic enzymes and thermostability of the CS clearly suggested that the bioactive substances had proteinaceous structures and hence classified as bacteriocins. The fact that Enterococcus faecalis N1-33 was isolated from edible fermented bamboo shoot together with these desirable physicochemical properties of its bacteriocin-activity and its ability of metabolizing low cost carbohydrates strongly suggested its great potential for use in food biopreservation. This was known to be the first report of the production of bacteriocins from LAB of fermented bamboo shoot.